Enriched conditioning expands the regenerative ability of sensory neurons after spinal cord injury via neuronal intrinsic redox signaling - Francesco De Virgiliis (Nature Portfolio, 2020)
Pre conditioning injury or environmental enrichment have been shown to promote axon regeneration. Here the authors show that environmental enrichment, combined with preconditioning injury promotes regeneration via a redox signalling dependent mechanism.